Political personalization as a strategy: visual framing analysis of the political leadership of Isabel Díaz Ayuso on Instagram - Egea-Barquero , Marina; Zamora Medina, Rocío (Estudios sobre el Mensaje Periodístico, 2023)
This study analyzes the use of personalization as a digital strategy on Instagram to build political leadership of the president of the Community of Madrid, Isabel Díaz Ayuso. The research, based on the theory of visual frames (visual framing), includes a quantitative analysis of 662 posts published in two different stages of her political career: before and after becoming president. Results show that, although Ayuso strategically offered images in her official profile that favored her visibility and closeness as a political leader, she made partial use of personalization due to her commitment to a more professional role than personal or private, as well as she was framed more linked to the image of the ideal candidate for a state woman than to populist leadership. Significant differences were detected according to the specific moment, when she was only a candidate for the presidency compared to when she already took office.
Keywords: Visual Framing; Instagram; Political Leadership; Visual Political Communication; Personalization